Autonomous Robotics: A fresh Era of Implant Dentistry… is a reality! - Haidar, Ziyad (Journal of Oral Research, 2019)
Per-Ingvar Brånemark’s virtuoso encounter of “osseointegration” in 1952 and George A. Zarb’s outstanding long-term evidence-based efforts, presented in 1982 via the renowned “Toronto Conference on Osseointegration in Clinical Dentistry” revived the realm of dental implantology. The last decades witnessed a hungry integration of computerized tomographic scans, computer-aided design/computerassisted manufacturing (CAD/CAM) and three-dimensional (3-D) surgical planning software, in practices and academic/training programs. With such oro-dental appliances that transfer the computerized planning into the surgical field, the oro-dental implantology field has been undergoing a remarkable and fast-paced trend towards minimallyinvasive surgical procedures.